Analysis of mechanical properties and its associated fracture surfaces in dual‐phase austempered ductile iron. Issue 7 (11th April 2013) - Basso, A.; Sikora, J.; Martínez, R.
ABSTRACT This work aims at evaluating the fracture surfaces of tensile samples taken from a new kind of ductile iron referred to as 'dual‐phase Austempered Ductile Iron (ADI)', a material composed of ausferrite (regular ADI microstructure) and free (or allotriomorphic) ferrite. The tensile fracture surface characteristics and tensile properties of eight dual‐phase ADI microstructures, containing different relative quantities of ferrite and ausferrite, were studied in an alloyed ductile cast iron. Additionally, samples with fully ferritic and fully ausferritic (ADI) matrices were produced to be used as reference. Ferritic–pearlitic ductile irons (DI) were evaluated as well. For dual‐phase ADI microstructures, when the amount of ausferrite increases, tensile strength, yield stress and hardness do so too. Interesting combinations of strength and elongation until failure were found. The mechanisms of fracture that characterise DI under static uniaxial loading at room temperature are nucleation, growth and coalescence of microvoids. The fracture surface of fully ferritic DI exhibited an irregular topography with dimples and large deformation of the nodular cavities, characteristic of ductile fracture. Microstructures with small percentages of ausferrite (less than 20%) yielded better mechanical properties in relation to fully ferritic matrices. These microstructures presented regions of quasi‐cleavage fracture around last‐to‐freeze zones, related to the presence of ausferrite in those areas. As the amount of ausferrite increased, a decrease in nodular cavities deformation and a flatter fracture surface topography were noticed, which were ascribed to a higher amount of quasi‐cleavage zones. By means of a special thermal cycle, microstructures with pearlitic matrices containing a continuous and well‐defined net of allotriomorphic ferrite, located at the grain boundaries of recrystallised austenite, were obtained. The results of the mechanical tests leading to these microstructures revealed a significant enhancement of mechanical properties with respect to completely pearlitic matrices. The topographies of the fracture surfaces revealed a flat aspect and slightly or undeformed nodular cavities, as a result of high amount of pearlite. Still isolated dimple patterns associated to ferritic regions were observed.